Hydropriming Improves Germination and Plant Recovery During Embryo Rescue of Wild Banana Musa acuminata var. tomentosa - Prawestri, Apriliana Dyah; Riastiwi, Indira; Rahayu, Resa Sri; Handayani, Tri; Leksonowati, Aryani; Poerba, Yuyu Suryasari (Jurnal Biodjati, 2021)
Wild bananas are believed to have genes for resistance to biotic and abiotic stress in nature, making them potential genetic resources for creating superior varieties. Wild banana seeds, such as Musa acuminata var. tomentosa are generally difficult to germinate in vivo, so that in vitro embryo culture technique is needed. This study aimedÂ to increase embryo germination and regeneration of wild banana M. acuminata var. tomentosa by soaking the seeds as hydropriming. The treatment comprised of soaking the seeds in sterile distilled water for four periods of time: 0 (control), 1, 4, and 7 days. A total of 45 embryos for each treatment were planted on petri dishes containing MS + 0.5 mg/L BA + 1 mg/L biotin + 1 mg/L proline. The results showed that hydropriming increased the rate of embryo germination and regeneration. Seeds soaked for 1, 4, and 7 days successfully resulted in embryoÂ germination percentagesÂ of 87%, 62%, and 62%, respectively, while the control unsoaked seeds germinated with a lower percentage of 42%. One-day soaking treatment was the most optimal treatment to increase the rate of germination and regenerationÂ as well asÂ obtained the best vigor as demonstrated by the highest average height of plantlets, number of leaves, and roots than other treatments. Thus, 1-day seed hydropriming is the best treatment for embryo rescue and regeneration of wild banana M. acuminata var. tomentosa